Obesity in Australia. Issue 1 (January 2018) - Huse, Oliver; Hettiarachchi, Janitha; Gearon, Emma; Nichols, Melanie; Allender, Steven; Peeters, Anna
Summary: Objectives: To describe prevalence and trends for overweight and obesity in Australia and to critique the quality of available data on this public health priority. Design: Comparison of aggregate prevalence data on adult and childhood overweight and obesity in publicly available national or state-based cross sectional surveys and survey series. Participants: All representative population surveys, conducted since 1995, with measured height and weight at a national or state level. Results: The most recent measured data found that 63.4% of Australian adults and 27.6% of children were overweight or obese in 2014/15. Tasmania had the highest observed adult prevalence of obesity (32.3%) and of overweight and obesity combined (67.5%). The Australian Capital Territory had the lowest observed prevalence of obesity (23.9%) and of overweight and obesity combined (63.0%). Between 2007/08 and 2014/15, the age-standardised prevalence of adulthood overweight and obesity combined increased from 64.4% to 66.4%. Across states/territories the observed change varied from −5.3% (Western Australia) to 6.0% (Queensland). Amongst children the observed prevalence of overweight and obesity combined increased from 24.7% to 27.6%. Across states/territories the observed change varied from −1.4% (South Australia) to 11.1% (Tasmania). Conclusions: In Australia, 1 in 10 more adults are obese today compared to 1995. Limitations in the available data mean it is difficult to conclude on trends over time in children, Indigenous Australians, or by state/territory. We need to ensure the continuation and expansion of our National Health Survey and/or explore novel monitoring options from other countries.